PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE WRITE PAIR SWITCH PEMAHAMAN KONSEP MATEMATIKA - Miftah Kurnia (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding the concept is one of the goals in learning mathematics. In fact, students’s concept understanding in class VIII SMPN 34 Padang has not developed optimally. This can be seen from the results of observations and tests given to students. Efforts to overcome these problems is to apply cooperative learning model Write Pair Switch type. The kind of this research is Quasi Experiment with Static Group Design. Sampling was done by random sampling technique. The instrument used is a test of essay. Based on the results of the test data analysis we can conclude that the ability of understanding the mathematical concepts of students which learn with cooperative learning type Write Pair Switch type is better than those learning with conventional learning. Thus, it can be said that there is the influence of cooperative learning model type Write Pair Switch to understanding students' mathematical concepts.Keywords – Understanding of mathematical concepts, Write Pair Switch, Conventional Learning